2010
DOI: 10.1007/s00246-010-9776-8
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Variation in Aortic Blood Flow Velocity as a Predictor of Fluid Responsiveness in Children After Repair of Ventricular Septal Defect

Abstract: This study aimed to compare respiratory variation in transthoracic echo-derived aortic blood flow velocity (∆Vpeak) and inferior vena cava diameter (∆IVCD) with central venous pressure (CVP) as predictors of fluid responsiveness in children after repair of ventricular septal defect (VSD). A prospective study conducted in pediatric intensive care unit investigated 21 mechanically ventilated children who had undergone repair of VSD. Standardized volume replacement (VR) was the intervention used. Hemodynamic meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 14 publications
4
88
0
3
Order By: Relevance
“…64 In small children, variation in blood-flow velocity in the aorta using echocardiography can serve as a surrogate for arterial pressure variations. 52,53 Arterial pressure variations are a reliable indicator of fluid responsiveness in adults. 51,65,66 However, reliability decreases with spontaneous respiration, nonsinus rhythm, pulmonary hypertension, right heart failure, low tidal volume, or open-chest conditions.…”
Section: Fluid Responsivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…64 In small children, variation in blood-flow velocity in the aorta using echocardiography can serve as a surrogate for arterial pressure variations. 52,53 Arterial pressure variations are a reliable indicator of fluid responsiveness in adults. 51,65,66 However, reliability decreases with spontaneous respiration, nonsinus rhythm, pulmonary hypertension, right heart failure, low tidal volume, or open-chest conditions.…”
Section: Fluid Responsivenessmentioning
confidence: 99%
“…Results from adult and pediatric studies have shown that only up to half of the fluid challenges increase SV. [51][52][53] To avoid unnecessary fluid overload, there is a great interest in predicting fluid responsiveness. Both static and dynamic parameters are used for this purpose.…”
Section: Fluid Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in infants and neonates have shown that fluid responders did not have an associated rise in blood pressure. 65,[69][70][71][72] Monitors of end organ perfusion have been used to titrate fluid therapy. Near infrared spectroscopy (NIRS) has shown that a systolic blood pressure fall of 37% from baseline is associated with significant cerebral desaturation.…”
Section: Dynamic Parameters -Any Use In Neonates?mentioning
confidence: 99%
“…Dynamic preload indicators, such as arterial pulse pressure variation (DPP), are variables that quantify the effects of mechanical ventilation on cardiac stroke volume, and have been shown in adults to predict VR [5][6][7]. Pediatric studies examining dynamic preload indicators [8][9][10][11] have found that respiratory variations in aortic blood flow predict VR in children.…”
Section: Introductionmentioning
confidence: 98%